GAMBARAN PENGETAHUAN IBU HAMIL MENGENAI TANDA BAHAYA KEHAMILAN DI UPT PUSKESMAS ULAWENG - Asriani Tahir (Jurnal Suara Kesehatan, 2021)
Abstract. Pregnancy danger signs are signs or symptoms that indicate a mother or baby is in danger. Every pregnancy in its development runs the risk of experiencing complications or complications. If a pregnant woman does not do an examination, it will not be known whether her pregnancy is going well, is at high risk or obstetric complications that can endanger the life of the mother and the fetus, so that it can increase morbidity and high mortality.Purpose To know the description of knowledge of pregnant women regarding the danger signs of pregnancy at UPT Puskesmas Ulaweng. Methods This type of research used in this study is a descriptive study. Descriptive research method is a research method that is carried out with the main objective of making an objective description or descriptive of a situation. So that the number of samples that meet the criteria is determined as many as 30 people.Results The results showed that 1) The knowledge of pregnant women about vaginal bleeding was in the good category, namely 24 people (80%). 2) Knowledge of pregnant women about premature rupture of membranes is in the good category, namely 20 people (67%). 3) Knowledge of pregnant women about severe abdominal pain in the good category, namely 17 people (57%). 4) Knowledge of pregnant women about excessive vomiting was in the good category, namely 14 people (46%).Conclusion Knowledge of Pregnant Women Regarding Pregnancy Hazard Signs at UPT Puskesmas Ulaweng is in a good category.